Structural challenges in developing entrepreneurial programs for undergraduates in Nigerian universities: A concern for educational planners - Sheyin, Adejoke Olabisi (International Journal on Education Insight, 2025)
Entrepreneurial programs in higher education play a vital role in equipping students with the skills, knowledge, and mindset necessary for success in today’s dynamic and competitive business environment. This study explores the key elements of successful entrepreneurial programs in Nigerian universities, highlighting their importance in fostering innovation, economic growth, and social change. It examines the challenges faced in the development of such programs, including curriculum limitations, inadequate resources, and a lack of experiential learning opportunities. Drawing on existing literature and theoretical frameworks, such as Experiential Learning Theory, this paper underscores the need for a comprehensive, hands-on approach to entrepreneurship education that emphasizes creativity, risk-taking, and problem-solving. It further recommends strategies for enhancing entrepreneurial programs, such as curriculum innovation, stronger mentorship networks, improved access to resources, and fostering a culture of resilience. The findings suggest that well-structured entrepreneurial programs can significantly contribute to job creation, economic development, and the cultivation of socially responsible entrepreneurs. By addressing the structural challenges and incorporating best practices from successful global programs, Nigerian universities can create an entrepreneurial ecosystem that empowers students to launch successful businesses and drive sustainable economic progress.